Mapping the E-Government Portrait of Malang City: A Cross-Platform Meta-Synthesis of Sixty Public Administration Undergraduate Theses, 2024–2025 - Bayu Indra Pratama; Muhammad Rizki Pratama (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study proposes a qualitative meta-synthesis framework applied to sixty undergraduate theses from Universitas Brawijaya graduating in 2024–2025 that examine e-government practice in Malang City. Drawing on Noblit and Hare’s meta-ethnography, eMERGe reporting, and PRISMA 2020 corpus selection, the work maps the corpus across at least twenty-three municipal digital platforms, reads each thematic cluster substantively, and weaves seven preliminary line-of-argument patterns. Citizen-interface depth predicts platform success more strongly than architectural completeness; nationally mandated platforms yield thinner local public value than locally originated ones; and a co-production gap pervades the corpus except in the disability-inclusion cluster. The framework offers theoretical, methodological, and practical contributions.